Pengaruh Adaptasi Mahasiswa Baru Terhadap Metode Pembelajaran pada Kesehatan Mental dan Fisik Mahasiswa di Fakultas Keolahragaan - Hartalena Sinaga; Mahiroh Lubis; Ritayana Silalahi; Talenta N. D. Simatupang (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
This study aims to analyze the influence of new students' adaptation to learning methods on campus, especially in sports study programs, and its implications for students' mental and physical health. This study uses a qualitative approach with observation and interview methods with seven female students of the Faculty of Sports, State University of Medan. The results of the study indicate that students experience high academic pressure due to the KKNI-based learning method and the block system, which has an impact on increasing stress levels, physical fatigue, and difficulties in managing study time between theory and practice. The implications of this study are relevant in developing student-friendly learning policies in order to maintain a balance between academic demands and their mental and physical health.